Transhuman contexts: AI, among others, in the School of Changes - Turpín Saorín , José (2025)
We will talk about what is meant by transhumanisms and once it is crumbled we will approach to talk about contexts and specifically among the plausible contexts, we stay in the school, a school that will opt for its transforming action at the same time as a place of meeting and assembly of realities that are and shape us. And where the new technologies, with AI at the forefront, build certain subjects destined to be what? A here and now full of possibilities in which we cannot ignore; future forms of life in a school of changes. Well... we have to know to better understand and understand to make good decisions, and why not, reformulate new educational approaches that prepare our students and propose to inhabit, humanly, a anthropotechnical world?